EFFECT OF DIFFERENT CULTURE MEDIA ON THE GROWTH AND CHLOROPHYLL-a CONTENT OF Navicula sp. and Synechococcus sp - Haslianti; Wa Ode Nilda Arifiana Effendy; Suwarjoyowirayatno; La Ode Baytul Abidin; Muhaimin Hamzah; Asmariani; Fatmawati; Wa Ode Intiyani Mangurana; Herlan Hidayat; Asjun (SEAMEO BIOTROP, 2026)
ARTICLE HIGLIGHTS- Walne medium significantly enhances microalgae growth and chlorophyll-a content.- F2+Si medium effectively supports Navicula sp. growth in cultivation.- Urea+NPK limits microalgae due to nutrient deficiency.- Optimal media selection is crucial for tropical microalgae cultivation. ABSTRACTThis research addressed a critical knowledge gap regarding the optimal cultivation conditions for indigenous microalgal strains from high-biodiversity tropical marine ecosystems, offering insights into their physiological responses to varied nutrient regimes. In particular, this study focused on evaluating the effect of three different culture media (Walne, F2+Si, and Urea+NPK) on the growth and chlorophyll-a content of local microalgae isolates, Navicula sp. and Synechococcus sp., isolated from Southeast Sulawesi waters. The isolates were cultivated at a laboratory scale in January 2025 using 250 mL Erlenmeyer flasks containing 100 mL of media, under continuous aeration at room temperature (26 - 30 °C) and constant illumination (90 µmol photons/m²/s). Growth was monitored every two days. The results demonstrated that Walne medium yielded the highest cell density and chlorophyll-a content for both species. In Walne medium, Navicula sp. reached a peak density of 8,656,000 ± 53,777 cells/mL with a specific growth rate (SGR) of 1.1453 ± 0.033, while the density of Synechococcus sp. reached 4,965,833 ± 16,646 cells/mL with an SGR of 0.8297 ± 0.032. The F2+Si medium also supported good growth, particularly for Navicula sp. (SGR of 1.0967 ± 0.003). However, the Urea+NPK medium consistently produced the lowest results for all parameters due to limitations in micronutrient and vitamin. One-Way ANOVA revealed no significant difference (P > 0.05) between Walne and F2+Si media for the growth of Navicula sp., but Walne medium was significantly superior for Synechococcus sp. This study concluded that the choice of the culture medium is crucial for optimizing microalgal growth. Walne medium is recommended as the optimal medium for cultivating both Navicula sp. and Synechococcus sp., whereas F2+Si serves as an effective alternative for Navicula sp. The findings underscore the importance of comprehensive nutrient formulations for maximizing biomass yield in local isolates and provide a foundation for developing cost-effective cultivation strategies in tropical regions.